Empirical Study of Specific Value Added Tax Problems in Selected European Union Member States - Danuše Nerudová; Petr David (European Financial and Accounting Journal, 2008)
Empirical study of specific value added tax problems in selected EU member states is focused mainly on the field of providing services. Specifically services provided to a person from the same EU member state, which shall provide this service immediately further to a customer from other EU member state and further provision of service provided by a provider from one EU member state to a recipient of service from other EU member state are concerned and also these services are connected with immovable property situated in the state of provider of service. These issues are solved in the frame of selected EU states – Czech Republic, Slovakia, Hungary and United Kingdom. The results show insufficiencies in treatment of the mentioned field of value added tax not only at the EU level, but also at the national level of the selected states and application of objective provisions in practice as well. General recommendations of process of elimination of insufficiencies causing problems in providing service further or providing service connected with immovable property are here on this base laid down. Except above mentioned facts, this paper also offers wider view on the harmonization process in the field of value added tax in the EU and highlights the significance of value added tax in the general consequences.
Keywords: H25; 650; VAT; Services provided further; Services connected with immovable property